Development of professionalism of the future teachers of art disciplines tn a context of modernization of modem education. - Nechayeva, L.V. (Pedagogy of Higher and Secondary Education, 2006)
The article throws the light to the questions of modernization of professional preparation of future teachers of artistic subjects. The author pays much attention to the importance of their mastering of art as the conception basis of the development of their artistically thinking.